Endorphin, Oxytocin, And Suggestive Massage Stimulation (SPEOS) Methods In Increasing Breast Milk Production In Postpartum Mothers - Ranida Arsi; Sri Rejeki; Achmad Zulfa Juniarto (Media Keperawatan Indonesia, 2021)
Postpartum pain and fatigue, impaired mobility, motivation, and psychological disorders of mother cause disturbances in the excretion of the breast which have an impact on the health of mother and baby. The SPEOS (Endorphin, Oxytocin, and Suggestive Massage Stimulation) methods is an alternative to help increase breastfeeding that combination of endorphin, oxytocin, and suggestive massage stimulation carried out sequentially which will feel the relaxation that stimulates the brain to release endorphin, prolactin and oxytocin hormones so that breast milk becomes smooth. The objective of this study to determine the effectiveness of the SPEOS methods in increasing breast milk production in postpartum mothers. A literature review through a review of nursing articles to identify SPEOS methods in increasing breast milk production in postpartum mothers. The author identifies research questions, identifies relevant articles, select articles, maps data and summarizes, analyzes and reports data. The databases used are Scopus, Medica Local Update, One Search and Google Scholar. Articles were filtered according to the inclusion and exclusion criteria. 7 articles include the inclusion and exclusion criteria requirements, then the article was synthesized to see which was affected by SPEOS method, the duration of the SPEOS method, and the time the SPEOS method war administered. This literature review shows that the SPEOS methods effective in increasing breast milk production in postpartum mothers. The SPEOS method not only helps physically but psychologically through oxytocin, endorphin massage, and suggestive. The SPEOS method is carried out for a minimum of 3 days to get an increase in milk production. This method should be done 2 times a day for maximum results for at least 14 minutes. The SPEOS methods are effective in increasing breast milk production in postpartum mothers.